Peran Pendidikan Kewarganegaraan dalam Memperkuat Digital Right dan Tanggung Jawab Warga Negara - Angraini, Rita; Ersya, Muhammad Prima (Journal of Civic Education, 2024)
This article analyzes the role of civic education in enhancing citizens' digital rights and responsibilities, emphasizing the need for wise use of technology. While citizens have the freedom to access internet technology, they are equally obliged to act responsibly and respect others when using it. This study adopts a conceptual approach by reviewing relevant articles and books. The analysis highlights that civic education plays a pivotal role in fostering responsible digital behavior. Civic education holds a strategic position in preparing citizens to meet global challenges, particularly through initiatives such as integrating digital citizenship topics into the national education curriculum. It also recommends innovations in digital-based learning models and emphasizes the importance of training and workshops for teachers. These initiatives aim to equip educators with the ability to adapt to new digital environments, encourage creativity, provide constructive feedback, and utilize various digital platforms effectively in the learning process. By embedding these practices, civic education can significantly contribute to creating informed, responsible digital citizens capable of balancing their rights and obligations in the digital age.